Pengaruh Store Atmosphere dan Word of Mouth Promotion Terhadap Keputusan Pembelian Pada Cafe Kopi Pedalaman Jambi - Sefti Gultum Miranda (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2021)
This study aims to determine how the influence of store atmosphere and word of mouth promotion on purchasing decisions at Café Kopi Pedalaman Jambi. The independent variables in this study are Store Atmosphere ( ), and Word of Mouth Promotion ( ), while the dependent variable in this study is Purchase Decision (Y). This research is a causal research using a quantitative approach using a questionnaire. The population of this study are consumers who have already purchased products at Café Kopi Pedalaman Jambi. The sampling technique was random sampling with a sample of 100 respondents. The analysis technique used in this study is multiple linear regression analysis using SPSS version 21.0 software. The results showed that simultaneously and partially each variable had a significant effect on purchasing decisions, and the most dominant variable that influenced purchasing decisions was the Word of Mouth Promotion variable because one of the indicators had a very high category. Judging from the results of the research, Word of Mouth Promotion has a positive and significant influence on purchasing decisions, it is better if the management of the Jambi inland coffee Café needs to add to the variety of products offered so that it is hoped that consumers who visit there can taste and enjoy more various kinds of products. available and can make consumers talk or spread good information to other potential customers.